Miami-Dade County Public Schools Campus Shield Evaluation, Miami, Florida, United States, 2014-2019 - McCrary, Joseph L. (Joseph Lorn) ([Verlag nicht ermittelbar], 2020)
In 2015, Miami-Dade County Public Schools (M-DCPS) received a three-year Comprehensive School Safety Initiative grant from the National Institute of Justice to implement, pilot test, and experimentally evaluate the effects of an innovative fusion center, Campus Shield, for proactively identifying and addressing school safety threats and issues. Three additional resources were also proposed to supplement and enhance the Campus Shield fusion center: visitor management systems (information on entries and exits from the school building to be recorded and fed into Campus Shield), surveillance cameras (which would also feed into Campus Shield), and the linkage of Campus Shield to "Mental Health Specialists" to provide direct services and act as a liaison between school-based student services professionals and community-based providers.